Factors affecting the daily feed intake and feed conversion ratio of pigs in grow-finishing units: the case of a company. Issue 1 (December 2016) - Pierozan, C.; Agostini, P. S.; Gasa, J.; Novais, A.; Dias, C.; Santos, R.; Pereira Jr, M.; Nagi, J.; Alves, J.; Silva, C.
Abstract Background The aim of this study was to use mathematical modeling to identify and quantify the main factors that affect daily feed intake (DFI) and feed conversion ratio (FCR) in grow-finishing (GF) pig units. We evaluated the production records of 93 GF farms between 2010 and 2013, linked to a company, working in a cooperative system, located in western Paraná State, Brazil. A total of 683 batches, consisting of approximately 495, 000 animals, were used. Forty production factors related to the management, health, plant and equipment, nutrition, genetics and environment were considered. The number of pigs per pen, type of feeder, origin and sex (the last two variables were combined in the models) of the animals and initial and final body weights were included in the final models to predict DFI and FCR (dependent variables). Additionally, the duration of the GF phase was included for the parameter FCR. All factors included in the final models had significant effects for both dependent variables. Results There was a reduction in DFI (0.04 kg) (P < 0.001) and an improvement in FCR (6.0 points) (P < 0.001) in batches from pens with less than 20 animals compared with batches from pens with more than 20 animals. In barns with "other" feeder types (mostly the linear dump type) different of conical semiautomatic feeder, a reduction of DFI (0.03 kg) (P < 0.05) and improved FCR (3.0 points) (P < 0.05) were observed. Batches of barrows from units specialized for producing piglets (SPU) had higher DFI (approximately 0.02 kg) (P < 0.01) than batches of females and batches of mixed animals from SPU, and batches of mixed animals from farms not specialized for piglet production (farrow-to-finish farms). Batches of females from SPU and mixed batches from SPU had better FCR (5.0 and 3.0 points respectively) (P < 0.001 and P < 0.001, respectively) than batches of piglets originating from farrow-to-finish farms. The variables selected for the final models explained approximately 50 and 64 % of the total variance in DFI and FCR, respectively. Conclusions The models are tools for the interpretation of the factors related to the evaluated parameters, aiding in the identification of critical aspects of production. The main parameters affecting DFI and FCR in this company during the GF period were the number of pigs per pen, the type of feeder used and the combination origin-sex of the animals.